Advancing Abalone Nutrition: The Science and Benefits of Formulated Feeds - Nur, Kurniati Umrah (Jurnal Ilmiah PLATAX, 2024)
The aquaculture industry has increasingly turned to formulated feeds to enhance the growth and health of abalone, a valuable marine species. This paper reviews the current state of research on abalone nutrition, focusing on the development and benefits of formulated feeds. The nutritional requirements of abalone are examined, highlighting the essential macro- and micro-nutrients needed for optimal growth. Various ingredients and additives used in feed formulations are discussed, along with the effectiveness of different feed types. The performance of formulated feeds is compared to natural diets, considering factors such as growth rates, health indicators, and environmental impact. Challenges in digestibility, palatability, and cost-effectiveness are addressed, and recent innovations in feed formulation techniques are explored. The review identifies gaps in current research and suggests directions for future studies to further advance abalone nutrition. Overall, formulated feeds are shown to offer significant benefits in terms of growth performance and sustainability, making them a promising solution for the future of abalone aquaculture.